Depolarization affects the lateral microdomain structure of yeast plasma membrane - Herman, Petr; Vecer, Jaroslav; Opekarova, Miroslava; Vesela, Petra; Jancikova, Iva; Zahumensky, Jakub; Malinsky, Jan (The FEBS journal, 2015)
We report the transmembrane voltage-induced lateral reorganization of highly-ordered lipid microdomains in the plasma membrane of living Saccharomyces cerevisiae. Using trans-parinaric acid (all-trans-9,11,13,15-octadecatetraenoic acid) as a probe of lipid order and different methods of membrane depolarization, we found that depolarization always invokes a significant reduction in the amount of gel-like microdomains in the membrane. Different depolarization mechanisms, including the application of ionophores, cell depolarization by an external electric field, depolarization by proton/hexose co-transport facilitated by HUP1 protein and a reduction of membrane potential caused by compromised respiration efficiency, yielded the same results independently of the yeast strain used. The data suggest that the voltage-induced reorganization of lateral membrane structure could play significant role in fast cellular response to acute stress conditions, as well as in other membrane microdomain-related regulatory mechanisms.
Keywords: Membrane Microdomains; Saccharomyces cerevisiae - proteiny; Membrane Potentials; Cell Membrane; membránové mikrodomény; Saccharomyces cerevisiae Proteins; Saccharomyces cerevisiae; buněčná membrána; membránové potenciály